Kairos in Innovation Policy: Theoretical Background and Practical Implications for the Triple Helix - Michael Rothgang; Bernhard Lageman (Triple Helix, 2021)
A kairos constellation designates a temporarily existing opportunity for a group of actors to take advantage of a coincidence of favourable circumstances in order to realise a shared target. Starting from the observation that kairos constellations are ubiquitous in human individual and social life, the research question of this paper is how the Triple Helix and the wider innovation policy research literature deals with such constellations. The authors develop a conceptual framework for kairos constellations and discuss empirical evidence that kairos constellations have been scrutinized in innovation research literature. Then, the concept is applied to an example from the Triple Helix – based cluster policy. The key message of this paper is that Triple Helix researchers should systematically study kairos constellations because they are a critical force in the evolution of innovations systems as well as business firms, which has not yet been systematically examined.
Keywords: 330; Cluster policy; Innovation policy; Path dependence; Triple helix; Window of opportunity